Re-energizing VHS Collections, Expanding Knowledge: A Conversation about VHS Archives - Juhasz, Alexandra; McCoy, Jennifer (KULA, 2018)
Scholars, activists, researchers, and artists of a certain age and inclination are burdened with a soon-to-be-obsolete but always-beloved, carefully tended but perhaps recently quieted collection that most likely sits on an office shelf gaining dust: their VHS Archive. Not a personal collection, but a professional one of continuing or even growing value if not usability, this archive has been lovingly built and used, probably over decades, for teaching and research and in support of the movements and issues that have mattered most to the collector. With the help of an Open Education Resources grant from CUNY we built an online teaching resource for a graduate course that would focus on just twelve of these tapes. We hope that the course and its lasting website asks, and will offer some answers about, best practices for reactivating knowledge that might be endangered due to medium obsolescence, and other broader cultural factors of forgetting.